Design of tri‐notched UWB antenna based on elliptical and circular ring resonators. Issue 3 (18th December 2018) - Rahman, Saeed Ur; Cao, Qunsheng; Li, You; Gil, Ignacio; Yi, Wan
Abstract: This article presents the design of a compact coplanar waveguide (CPW) fed Monopole Antenna for ultra‐wideband (UWB) applications. The semi‐circular shaped radiator is fed with a 50‐Ω line that resonates within the UWB frequency range. Two notching elements are used to reduce narrowband interferences. An elliptical ring resonator is etched out from the radiator to suppress 3.97‐4.48 GHz narrowband interference whereas, narrow bands from 5.79 to 6.57 GHz (WLAN) and 7.30‐7.60 GHz (X band downlink) were suppressed by loading a metamaterial inspired circular ring resonator behind the feed line. Moreover, the lower notching band due to the elliptical ring resonator can be further tuned to lower resonance frequencies by controlling the capacitance of the embedded varactor diode. The antenna has a compact size of 36 × 34 × 1 mm 3 . The antenna is simulated, fabricated and measured in an Anechoic Chamber. The measured results are in good agreement with the simulated results.